Teacher evaluation to enhance professional practice - Danielson, Charlotte; McGreal, Thomas L.; ebrary, Inc. (Alexandria, Va. : Association for Supervision & Curriculum Development, 2000)
Offers a guide to an effective teacher evaluation system that combines quality assurance with professional development.
Includes bibliographical reference and index.
Keywords: Teachers -- Rating of -- United States; Teaching -- Evaluation -- United States